2022
DOI: 10.1039/d1ja00374g
|View full text |Cite
|
Sign up to set email alerts
|

Improved uranium isotopic ratio determinations for the liquid sampling-atmospheric pressure glow discharge orbitrap mass spectrometer by use of moving average processing

Abstract: Applying moving average processing to isotope ratio determinations collected using an LS-APGD source coupled with an Orbitrap MS increases the precision of the measurements and reduces the number of points needed to collect high precision data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Specifically, the use of a moving average processing (akin to Savitzky-Golay or moving boxcar processing) of the derived isotope ratio values has been investigated. 31 The use of a moving average (of data windows of various widths) improves the precision of the ratio measurements and reduces the number of scans needed to be collected to generate high-precision results. It is believed that the approach holds promise for other quantitative measurements on FT-MS (ICR and Orbitrap) instruments as well.…”
Section: Advanced Data Acquisition and Signal Processing Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, the use of a moving average processing (akin to Savitzky-Golay or moving boxcar processing) of the derived isotope ratio values has been investigated. 31 The use of a moving average (of data windows of various widths) improves the precision of the ratio measurements and reduces the number of scans needed to be collected to generate high-precision results. It is believed that the approach holds promise for other quantitative measurements on FT-MS (ICR and Orbitrap) instruments as well.…”
Section: Advanced Data Acquisition and Signal Processing Approachesmentioning
confidence: 99%
“…Moving (i.e., boxcar) averaging of data windows and widths also provided improved quantitative and ratio performance reducing measurement times and analyte/sample consumption. 31,32,33 Together, the collaborative body of work has clearly demonstrated that high precision isotope ratio results for U and other elements can be achieved with a simple, low cost, glow discharge ion source coupled to an Orbitrap MS. Additionally, and interestingly, Eiler and co-workers (Caltech) 32,33 and others 34,35 have demonstrated effective results for low mass stable isotope analyses (including those for C, H, N, and S) on small inorganic and organic/ molecular compounds and mixtures using Orbitrap MS techniques (a significant advantage over other stable isotope MS approaches that require separation and presentation of pure gaseous forms of these elements).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work with the LS-APGD coupled with a benchtop Thermo Scientific Q Exactive Focus Orbitrap focused primarily on the challenging uranium isotope ratio determinations. ,,,,, A comparable level of performance was found across a wide range of uranium isotope depletion/enrichment levels during a first-level assessment of the LS-APGD-Orbitrap platform versus TIMS and scanning sector field and quadrupole ICP-MS isotope ratio determinations . Additional studies have looked at plasma discharge conditions, different collisional dissociation modalities, the effects of concomitant ions, advanced data acquisition systems, and data processing methods associated with uranium isotope ratio determinations. ,,,, The major incentive for exploring isotope ratio determination of uranium includes leveraging the high mass resolution offered by the Orbitrap mass spectrometer to overcome isobaric and molecular species interferences that thwart straightforward analysis with traditional MS techniques. The overarching goal here is the ability to perform concurrent uranium and plutonium determinations, with little-to-no sample pretreatment.…”
mentioning
confidence: 99%